2013
DOI: 10.3390/toxins5122589
|View full text |Cite
|
Sign up to set email alerts
|

Towards Clinical Applications of Anti-endotoxin Antibodies; A Re-appraisal of the Disconnect

Abstract: Endotoxin is a potent mediator of a broad range of patho-physiological effects in humans. It is present in all Gram negative (GN) bacteria. It would be expected that anti-endotoxin therapies, whether antibody based or not, would have an important adjuvant therapeutic role along with antibiotics and other supportive therapies for GN infections. Indeed there is an extensive literature relating to both pre-clinical and clinical studies of anti-endotoxin antibodies. However, the extent of disconnect between the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 173 publications
1
22
0
Order By: Relevance
“…The effectiveness of heat treatment was confirmed by inclusion of a control sample of plasma spiked with a 0·2 EU mL −1 final concentration of endotoxin standard. Because previous literature on endotoxaemia in HAT have presented endotoxin concentrations as lipopolysaccharide (LPS) equivalents, endotoxin concentrations were expressed as pg mL −1 LPS using the conversion 1 EU mL −1  = 100 pg mL −1 (Hurley, 2013). …”
Section: Methodsmentioning
confidence: 99%
“…The effectiveness of heat treatment was confirmed by inclusion of a control sample of plasma spiked with a 0·2 EU mL −1 final concentration of endotoxin standard. Because previous literature on endotoxaemia in HAT have presented endotoxin concentrations as lipopolysaccharide (LPS) equivalents, endotoxin concentrations were expressed as pg mL −1 LPS using the conversion 1 EU mL −1  = 100 pg mL −1 (Hurley, 2013). …”
Section: Methodsmentioning
confidence: 99%
“…In comparative studies with this model, a relatively avirulent strain of E. coli versus P. aeruginosa (48), Staphylococcus aureus (66), or a more virulent strain of E. coli (65) showed similar quantitative levels of bacteremia, whereas the associated hemodynamic changes and shortened survival times were in each case more severe than those observed in association with the avirulent E. coli strain, as would be expected (48,65,66). Surprisingly, despite these expected differences, in each study the levels of endotoxemia were 3-fold (65) to 10-fold (48) lower or even undetectable (46) versus the levels seen after challenge with the avirulent E. coli strain. Interestingly, endotoxins extracted and purified from the virulent and avirulent E. coli strains were equal with respect to potency and endotoxin amount per bacterium; hence, the lack of an association between endotoxemia and disease severity in this experimental model could not be explained on this basis (65).…”
Section: Figmentioning
confidence: 66%
“…Third, paradoxical observations among animal models of sepsis indicate that the concordance of endotoxemia with GN bacteremia and also with outcome is expected to differ for different GN bacteremia types (48). The detection of endotoxemia is of interest in relation to ongoing efforts to develop rapid detection methods for GN bacteremia and the possible application of emerging endotoxemia therapies (46). Finally, newer statistical methods have enabled a reappraisal over a broad range of assay breakpoints (49).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a randomized study of antiendotoxin antibody (HA-1A) conducted in children with meningococcal septicemia, no significant reduction in mortality was observed in children treated with HA-1A compared with placebo [27]. Subsequent studies in adults with gram-negative septicemia also showed no benefit of therapy with HA-1A [28]. In a randomized controlled trial of recombinant bactericidal permeability-increasing protein (rBPI 21 ), which binds and neutralizes endotoxin and blocks the inflammatory cascade, patients treated with rBPI 21 suffered fewer amputations, fewer blood product transfusions, and improved functional outcomes compared with those treated with placebo [29].…”
Section: Adjunctive Therapiesmentioning
confidence: 99%